A revision of the Australian cicada genus Punia Moulds, 2012 (Cicadidae: Cicadettinae: Cicadettini) with the description of four new species - Moulds, M.s. (Zootaxa, 2020)
Punia minima (Goding & Froggatt, 1904) from the Northern Territory is redescribed and the female described for the first time. Four new species found across the monsoonal north of Australia are documented: P. hyas sp.n., P. limpida sp.n., P. kolos sp.n. and P. queenslandica sp.n. A key to all five species is provided and their phylogenetic relationships discussed.